Experimental study of proton induced cross-sections on natural cadmium leading to the production of In-111 radionuclide - Khandaker, Mayeen Uddin; Kim, G.; Kim, K.; Lee, M.; Kim, K.S.; Lee, Y.S.; Cho, Y.S.; Lee, Y.O. (2008)
We measured the production cross-sections of In-111 induced by proton on the Cd-nat at several proton energies between 4 MeV and 40 MeV by using a stacked-foil activation technique at the MC50 cyclotron of the Korea Institute of Radiological and Medical Sciences. The present results were compared with the earlier reported experimental data and the theoretical calculations by using both the TALYS code and the ALICE-IPPE code. An overall good agreement was found with the recently reported experimental data and the TALYS prediction, as well. Integral yields of In-111 were also deduced from the measured cross-sections.